SUPERVISI KEPALA SEKOLAH UNTUK MENINGKATKAN KINERJA TENAGA PENDIDIK - Bashirotul Hidayah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2020)
Educational institutions as a forum for the intellectual life of the nation are required to make various efforts and innovations in order to improve the quality of education. As an institution, of course, schools must have learning tools and educators to carry out the learning process. In addition, schools must also have good and efficient institutional and employee governance. This is where the role of the principal is tested and required to be able to regulate and manage the school institution as well as all educators and academicians within the scope of the school so that they can progress and be organized as the vision and mission of the institution and to improve the quality of the school in a comprehensive and sustainable manner.